Comparison of physical activity and skinfold thickness of students living in rural and city center - Hüseyin Ö. Yurdakul; Barış Baydemir (IP Iermakov S.S., 2020)
Background and Study Aim. ln this academic research, it was aimed to compare the physical activity and skinfold thickness of the students living in the city center and rural areas. Material and Methods. 89 students attending the 6th grade level, whose total age is 12 years old, residing in the city center and rural areas of Çanakkale participated in the study. Students were examined with SenseWear armband bmi, total energy consumption, daily step count, met, active energy consumption, physical activity time, reach time and sleep times. Body mass index was determined with Holtain Skinfold Caliper. For the analysis of the dataset, the Independent Sample t test was utilized to examine the difference between the students' physical activity levels and skin fold thickness.  Then, the relevance between physical activity level and skinfold thickness was examined for pearson correlation. Significance value p<.05 and p<.01were accepted. Results. ln accordance with the data obtained with SenseWear Armband, it has been determined that a statistically substantial amount of difference between BMI total energy consumption und daily step number of students living in rural and city centers is present. According to the results of skin fold thickness measurements made with skinfold calipers, there was a significant difference in triceps, subscapular, abdominal, suprailiac and femur regions (p<.05). Conclusion. As a result of the research, it is concluded that students studying in the city center have less physical activity level than students living in the rural area.